Growth and survival of a diallel cross for five strains of climbing perch (Anabas testudineus Bloch, 1792) in Thailand - Piwpong, Nitikorn; Chiayvareesajja, Jarunee; Chiayvareesajja, Sommai (Agriculture and Natural Resources, 2016)
A complete diallel cross experiment was conducted with five strains of climbing perch (Anabas testudineus) representing three wild populations collected from main river basins in Thailand and two farm populations in southern Thailand. Growth performance was recorded from 794 individually tagged progeny of the 24 different strain combinations after a grow-out period of about 130 d in an earthen pond. Least squares means of body weight at harvest and absolute growth rates were computed for each strain combination. The Chumphon strain showed the highest growth performance (81.1 ± 1.1 g). The Surat Thani x Chumphon (the first strain represents the sire) showed the highest survival (65.4 ± 25.50%) among the purebreds and the crossbreds. The domesticated gene pool had much better growth in aquaculture than the wild gene pool. The correlation between the least squares means of body weight and the survival rates in the 24 strain combinations was 0.51 (p < 0.05). The mean heterosis of all crossbreds across traits was negative (-10.2 ± 22.7%). Heterosis appeared to decrease when different gene pools were crossed. This suggests that there may be outbreeding depression. The advantage of crossbred performance was clearly not shown in the study.